Anion binding, electrochemistry and solvatochromism of β-brominated oxoporphyrinogens. Issue 9 (3rd February 2016) - Webre, Whitney A.; Hill, Jonathan P.; Matsushita, Yoshitaka; Karr, Paul A.; Ariga, Katsuhiko; D'Souza, Francis
Abstract : A series of β-pyrrole brominated oxoporphyrinogens have been synthesized, and their physicochemical properties relevant to structure–activity are investigated. Abstract : Effects of macrocycle bromination on the structural, electrochemical and anion binding properties of 5, 10, 15, 20-tetrakis(3, 5-di- t -butyl-4-oxo-cyclohexa-2, 5-dienylidene)porphyrinogen, OxP, are reported. Bromination of 5, 10, 15, 20-tetrakis(3, 5-di- t -butyl-4-hydroxyphenyl)-porphinatocopper(ii ), [T(DtBHP)P]Cu(ii ) yieldedβ-Br8 OxP, which was N -alkylated toβ-Br8 OxPBz2 andβ-Br8 OxPBz4 (where Bz = 4-bromobenzyl).β-Br8 OxPBz2 crystallizes in orthorhombic space group Pccn [ a = 23.5535(17) Å, b = 19.3587(14) Å c = 20.9760(15) Å, V = 9564.3(12) Å 3 ]. It has a calix[4]pyrrole-like structure with a saddle conformation and two molecules of methanol occupy a central binding site made up of the non-alkylated pyrrole N–H groups. Computational and electrochemical studies revealed widening HOMO–LUMO band gaps for the brominated compounds over the non-brominated analogues consistent with the observed hypsochromic shifts in electronic absorption spectra. Solvatochromic and chromogenic effects on anion binding were both observed forβ-Br8 OxP andβ-Br8 OxPBz2 with binding affinities of anions being greater than those observed for the correspondingOxP andOxPBz2 . Colorimetric sensor studies suggest that theOxP compounds reported here are possible candidates for use in the design of optoelectronic noses for detection of anions and anionic analyte species of biological interest.